The Urgency of Disability Accessibility in Gorontalo District Government Agencies - Ismet Hadi; Upik Dyah Eka Noviyanti; Irwansyah Reza Mohamad; Mohamad Ilyas Abas (Borong Newinera Publisher, 2020)
Accessibility is the facilities provided for persons with disabilities to realize equality and opportunity and all aspects of life and livelihood as ease of moving through and using buildings and the environment with due regard to fluency and feasibility. The purpose of this study was to determine the Gorontalo District regional government policy in implementing the Act relating to the accessibility of the needs of persons with disabilities. Particularly on the accessibility of persons with disabilities to government agencies in Gorontalo District based on Law No. 8 of 2016 concerning Persons with Disabilities and universal design principles implemented in Ministerial Regulation No. 14 of 2017 concerning Building Easiness Requirements. This research uses a normative a juridical type of research with a juridical empirical approach. The results showed that (1). Implementation of Law No. 8 of 2016 concerning Persons with Disabilities in Gorontalo Regency has not been implemented optimally (2). Obstacles found in government agencies in the Gorontalo District environment include government buildings not yet accessible for persons with disabilities. This means that the facilities provided do not meet the universal design principles of ease, usefulness, safety, and independence. The absence of regulations in the form of Regional Regulations and Regents as a legal umbrella related to the standard facilities and services that must be provided for persons with disabilities, and the lack of local budgets for the development and construction of facilities related to the accessibility of persons with disabilities.